Molecular Cloning, Expression Analyses, and Physiological Roles of Cathelicidins in the Bursa of Fabricius of the Japanese Quail, Coturnix japonica - Takumi Ikeda; Hirotada Kondo; Daiki Nunomura; Genki Sato; Machi Ito; Nanako Yamanaka; Shawichi Iwamuro; Itaru Hasunuma; Sakae Kikuyama; Tetsuya Kobayashi (MDPI AG, 2023)
Antimicrobial peptides (AMPs) act directly on pathogens and maintain the anti-inflammatory effects and activation of immunocompetent cells. Therefore, the activation of the immune system in poultry via the elevation of endogenous AMPs has been attempted. In this study, we focused on the host defense mechanisms in the bursa of Fabricius (BF) of Japanese quail, cloned the cDNA of cathelicidin (CATH)-1 to -3, and analyzed their expression sites. In situ hybridization experiments revealed the mRNA expression of the CATHs in the interfollicular epithelium surrounding the lumen of the quail BF, which suggests that each CATH may exert its antimicrobial action directly in the BF. The intravenous injection of bacterial lipoteichoic acid and lipopolysaccharide endotoxins into the quail promoted the mRNA expression of CATH-1 and CATH-3 in the BF. The addition of CATH-1 or CATH-2 at the time of the antigen injection into mice resulted in antiserum with high antibody titers. Ad libitum administration of butyrate, a short-chain fatty acid, in the drinking water induced an increase in CATH-2 mRNA expression in the BF under certain conditions. These results may improve the defense mechanisms of quail by stimulating CATH expression in the BF through their diet.